Injectable AuNP-HA matrix with localized stiffness enhances the formation of gap junction in engrafted human induced pluripotent stem cell-derived cardiomyocytes and promotes cardiac repair. (December 2021) - Li, Hekai; Yu, Bin; Yang, Pingzhen; Zhan, Jie; Fan, Xianglin; Chen, Peier; Liao, Xu; Ou, Caiwen; Cai, Yanbin; Chen, Minsheng
Abstract: Cell therapy offers a promising paradigm for heart tissue regeneration. Human induced pluripotent stem cells (hiPS) and their cardiac derivatives are emerging as a novel treatment for post-myocardial infarction repair. However, the immature phenotype and function of hiPS-derived cardiomyocytes (hiPS-CMs), particularly poor electrical coupling, limit their potential as a therapy. Herein, we developed a hybrid gold nanoparticle (AuNP)-hyaluronic acid (HA) hydrogel matrix encapsulating hiPS-CMs to overcome this limitation. Methacrylate-modified-HA was used as the backbone and crosslinked with a matrix metalloproteinase-2 (MMP-2) degradable peptide to obtain a MMP-2-responsive hydrogel; RGD peptide was introduced as an adhesion point to enhance biocompatibility; AuNPs were incorporated to regulate the mechanical and topological properties of the matrix by significantly increasing its stiffness and surface roughness, thereby accelerating gap junction formation in hiPS-CMs and orchestrating calcium handling via the αn β1integrin-mediated ILK-1/p-AKT/GATA4 pathway. Transplanted AuNP-HA-hydrogel-encapsulated-hiPS-CMs developed more robust gap junctions in the infarcted mice heart and resynchronized electrical conduction of the ventricle post-myocardial infarction. The hiPS-CMs delivered by the hydrogels exerted stronger angiogenic effects, which also contributed to the recovery process. This study provides insight into constructing an injectable biomimetic for structural and functional renovation of the injured heart.